A framework for prioritizing the solutions to overcome sustainable manufacturing barriers - Javed Malek; Tushar N. Desai (Cleaner Logistics and Supply Chain)
The manufacturing sector can contribute significantly to the economic growth of any nation by adopting ingenious methods which can reduce negative environmental impacts. Sustainable manufacturing has gained enormous attention during the last decade for improving sustainable performance. For enhancing sustainable performances, manufacturing organizations need to overcome barriers to sustainable manufacturing. The present study has applied a three-level approach to identify barriers and solutions of sustainable manufacturing in manufacturing organizations. A combined approach of extensive literature analysis and the Delphi technique is utilized to finalize the barriers and solutions. The present study has identified 7 main barriers, 33 sub-barriers, and 27 solutions. The best worst method (BWM) is employed for the prioritization of finalized barriers. Financial and strategic barriers are the most significant barriers which hinder sustainable manufacturing adoption. The present study is an initiative to utilize extended Preference Ranking Organization METHod for Enrichment of Evaluations II (PROMETHEE2) for ranking the solutions of sustainable manufacturing. The ranking of solutions suggests “supportive governmental legislations” as the uppermost solution to overcome selected barriers. A sensitivity analysis is also executed to investigate the fitness of the final results of the present study. The present findings will enable the case organizations to identify the most obstructive barriers and also enable them to adopt solutions that can reduce the intensity of barriers. A comprehensive analysis of manufacturing organizations can be executed to compare the findings of the present work.